THE ROLE OF ACTIVE INVESTMENT POLICY IN ENSURING DECENT EMPLOYMENT - Nabiev O. A. (European Science Publishing, 2024)
Outdated work forms and methods in the field of employment, non-compliance of the established workplaces with the International Labor Organization's concept of Decent Work, superficial approach to employment of young people who have completed educational institutions, distortion of the real situation in the labor market by official statistical data, expansion of the scope of the "hidden economy" in the country, led to an increase in illegal labor migration and informal employment, and an increase in the unemployment rate. The article provides comments on these problems and solutions.
Keywords: investments, concept of Decent Work, informal employment, unemployment rate, precarious work.